Evaluasi Kinerja Alat Pengolahan Wet Belt Low Intensity Magnetic Separator (WBLIMS) Untuk Meningkatkan Kadar dan Recovery Sn di TB Primer Batubesi PT Timah Tbk Kabupaten Belitung Timur - Dimas Pangestu; Franto Franto; Janiar Pitulima (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2023)
Primary TB Batubesi Site a subsidiary of PT Timah Tbk, processes primary tin feed stockpile and SHP of oxide clay type using various tools, including the Wet Belt Low Intensity Magnetic Separator (WBLIMS). Currently, WBLIMS can only produce tin concentrate with a grade of 0.5-2% and a recovery of 5-8%, falling below the company's target of 8% grade and 15% recovery (XRF Test). This research conducted eight experiments with variations in feed types and rates. The WBLIMS feed from the stockpile has a Sn content of 0.62%, resulting in a tin concentrate with 1.21% Sn and a recovery of 7.05%. On the other hand, the feed from SHP has a Sn content of 0.61%, resulting in a tin concentrate with 0.95% Sn and a recovery of 5.11%. The type and rate of feed affect the increase in Sn grade and recovery. At low feed rates, the feed material yields lower Sn grade and recovery, while at high feed rates, the results are higher. Increasing the feed rate for WBLIMS from the stockpile leads to a decrease in Sn grade and recovery, whereas in the processing of SHP, the Sn grade increases but recovery varies. Experiments F1L1 and F2L3 yield the most optimal Sn grade and recovery, with F1L1 having a Sn grade of 2.28% and recovery of 11.54%, and F2L3 having a Sn grade of 2.87% and recovery of 9.24%. Although not reaching the company's target, these experimental results can enhance the Sn grade and recovery compared to the previous setup.